Histopathological Study of Non-Cirrhotic Portal Fibrosis (NCPF) With Special Emphasis on Advanced Fibrosis - Chaturvedi, Rachana; Shah, Tejal; Joshi, Amita; Mishra, Toshi; Karegar, Manjusha; Shukla, Akash (Annals of Pathology and Laboratory Medicine, 2018)
Background: Non-cirrhotic portal hypertension includes primarily the cases of non-cirrhotic portal fibrosis (NCPF) and extra-hepatic portal vein obstruction, both showing no significant parenchymal disease. NCPF is a disease of uncertain etiology characterized by periportal fibrosis with small and medium sized portal vein branches involvement. Most study done in the past are clinical, hence we decided to analyse its histo-pathological features with clinical correlation. Methods: This is four and half year’s retrospective study of liver biopsies of clinically diagnosed patients of NCPF. Fifteen patients of EHPVO served as controls. Biopsies were stained with Haematoxylin and eosin, reticulin and Masson’s trichrome. Result: Total 978 benign specimens (excluding space-occupying lesions) received, of which 45 diagnosed as NCPF (4.6%). Most patients (68.88%) were between 20-40 years (M:F ratio 1:1.5), commonest symptoms long-standing splenomegaly (95%), anemia (78%) and variceal bleeds (42%) with duration varying from 3 months to 11 years. Commonest histopathological findings were portal tract fibrosis (77.78%), phlebosclerosis (68.89%), portal tract remnants (24.44%), more frequently seen in NCPF than EHPVO, septal fibrosis was seen in five. Follow up available in 91.11% cases showed no mortality or liver failure, but significant morbidity due to repeated episodes of variceal bleeds and hypersplenism. Conclusion: NCPF is still common in India. Distinctive features on histology are portal tract fibrosis, portal tract remnants, with phlebosclerosis which is being statistically significant when comparing with EHPVO. NCPF can show advanced fibrosis, can also present with features of decompensation mimicking cirrhosis, however its course remains stable with good long-term survival.